Soil Health Changes Over a 25-Year Chronosequence From Forest to Plantations in Rubber Tree (Hevea brasiliensis) Landscapes in Southern Côte d'Ivoire: Do Earthworms Play a Role? - Tondoh, Jérôme E.; Dimobe, Kangbéni; Guéi, Arnauth M.; Adahe, Léontine; Baidai, Yannick; N'Dri, Julien K.; Forkuor, Gerald (Frontiers in Environmental Science, 2019)
The agro-ecological drawbacks of the spread of rubber tree plantations in Côte d'Ivoire since the 1990's are obvious even though they have not been properly investigated. They consist of biodiversity loss, land degradation and food insecurity, which have extended into the existing cocoa-led degraded areas whose rehabilitation have unfortunately not started. This situation increases not only the threat on soil health status but also undermines the capability of soils to deliver ecosystem services that are key to sustainable agricultural production. The current study took advantage of a chronosequence in rubber tree landscapes to assess soil health deterioration in general and possibly earthworm-mediated role in soil health changes. The hypothesis underpinning this study was that earthworms contribute to mitigate soil health deterioration in rubber-dominated landscapes due to their key role in soil functioning. This study confirmed that the conversion of forest to rubber tree plantations significantly impaired all soil biological, physical, and chemical parameters at the beginning (7 years) of the chronosequence; followed further by a restorative trend taking place beneath the plantations from 12 years. However, this study failed to find evidence of a direct role of earthworms in soil health rehabilitation over time. Mesoscale studies along with the use of appropriate models could help unravel this “black box” and shed some light on the contribution of earthworms as key soil ecosystem engineers.